2012
DOI: 10.1007/s11095-012-0770-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Engineered Nanoliposomes by Chelating Ligands for Modulating the Neurotoxicity Associated with β-Amyloid Aggregates of Alzheimer’s disease

Abstract: In vitro and ex vivo results elucidated the effectiveness of chelating ligand-bound NLPs for prevention of CuAβ(1-42) or ZnAβ(1-42) aggregate buildup associated with neurotoxicity in PC12 neuronal cells, as well as promotion of intracellular uptake in the presence of Cu(II) or Zn(II) metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…As determined by the 3D geometrical conformation and stabilization via molecular modeling, the addition of CHOL provided the much needed space filling properties to the ternary system wherein the van der Waals space of the molecular complex contributed to matrix stabilization. This change in H‐bonding dominated system to hydrophobically stabilized system was further responsible for the self‐assembly of the complex into nanoliposomes (nanoformation) when hydrated in phosphate buffered saline . Furthering the modeling paradigm of the effect of PEG on nanoformation, Tomar and coworkers discussed how using an amphiphilic PEG can assist in nanostabilization and nanoperformance.…”
Section: Nanoformation and Solvation Properties Of Polymeric Nanosystemsmentioning
confidence: 99%
“…As determined by the 3D geometrical conformation and stabilization via molecular modeling, the addition of CHOL provided the much needed space filling properties to the ternary system wherein the van der Waals space of the molecular complex contributed to matrix stabilization. This change in H‐bonding dominated system to hydrophobically stabilized system was further responsible for the self‐assembly of the complex into nanoliposomes (nanoformation) when hydrated in phosphate buffered saline . Furthering the modeling paradigm of the effect of PEG on nanoformation, Tomar and coworkers discussed how using an amphiphilic PEG can assist in nanostabilization and nanoperformance.…”
Section: Nanoformation and Solvation Properties Of Polymeric Nanosystemsmentioning
confidence: 99%
“…Another interesting study reported that nanoliposomes modified with different chelating ligands such as copper acetate, histidine, zinc acetate and ethylenediaminetetraacetic acid disaggregated and resolubilized Cu-Aβ 1-42 and Zn-Aβ 1-42 aggregates in PC12 neuronal cells. This finding suggests that chelating ligand-bound NPs can protect neuronal cells from Aβ aggregation-induced toxicity [22].…”
Section: Inhibition Of Aβ Aggregationmentioning
confidence: 89%
“…Mufamadi et al developed surface decorated nanoliposomes (NLPs) using different chelating agents viz. ethylenediaminetetraacetic acid (EDTA), histidine residues, copper acetate (CuAc) and zinc acetate (ZnAc) to modulate neurotoxicity associated with Aβ aggregates of AD [113]. The result of their in vitro studies in PC12 neuronal cell line confirmed that the incubation of Cu(II) or Zn(II) with Aβ 1–42 peptide stimulated Aβ aggregation.…”
Section: Nanotechnology Based Theranostics In Admentioning
confidence: 99%